2021
DOI: 10.1053/j.jvca.2021.02.061
|View full text |Cite
|
Sign up to set email alerts
|

Is Cerebral Oximetry Monitoring a Standard-of-Care During Cardiac Surgery?

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Previous studies reported benefits of NIRS monitoring outside the indications suggested by the guidelines 3,8 . This may suggest the routine use of NIRS for all cardiac surgical procedures 10 . Despite proposed algorithm-based approaches to re-establish NIRS baseline values 8,11 the incidence and types of specific interventions have been poorly reported in the literature.…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies reported benefits of NIRS monitoring outside the indications suggested by the guidelines 3,8 . This may suggest the routine use of NIRS for all cardiac surgical procedures 10 . Despite proposed algorithm-based approaches to re-establish NIRS baseline values 8,11 the incidence and types of specific interventions have been poorly reported in the literature.…”
Section: Introductionmentioning
confidence: 90%